Facility-level CKD-MBD composite score and risk of adverse clinical outcomes among patients on hemodialysis. Issue 1 (December 2016) - Block, Geoffrey; Yusuf, Akeem; Danese, Mark; Wirtz, Heidi; Hu, Yan; Do, Thy; Cooper, Kerry; Gilbertson, David; Bradbury, Brian; Collins, Allan
Abstract Background Patients receiving hemodialysis with values outside of target levels for parathyroid hormone (PTH: 150–600 pg/mL), calcium (Ca: 8.4–10.2 mg/dL), and phosphate (P: 3.5–5.5 mg/dL) are at elevated morbidity and mortality risk. We examined whether patients receiving care in dialysis facilities where greater proportions of patients have at least two values out of target have a higher risk of adverse clinical outcomes. Methods The study cohort consisted of 39, 085 prevalent hemodialysis patients in 1298 DaVita dialysis facilities as of September 1, 2009, followed from January 1, 2010, until an outcome, a censoring event, or December 31, 2010. We determined the quintile of the distribution across facilities of the proportion of patients with at least two of three parameters out of, or above, target over a 4-month baseline period. The primary composite outcome was cardiovascular hospitalization or death. Secondary outcomes included death, cardiovascular hospitalization, and parathyroidectomy. Poisson regression models were used to estimate the association of facility quintile with outcomes. Results Facility quintile was associated with a 7 % increased risk of cardiovascular hospitalization or death (quintile 5 versus 1, RR 1.07, 95 % CI 1.01–1.13) using the out-of-target measure of exposure and a 12 % increased risk (RR 1.12, 95 % CI 1.06–1.19) using the above-target measure. No association was seen for death using either measure. Patients in facility quintiles 3–5 (versus 1) were at increased parathyroidectomy risk (RR ranged from 2.05, 95 % CI 1.10–3.82, for quintile 3 to 2.73, 95 % CI 1.50–4.98, for quintile 5). Conclusions Facility level analysis of a large prevalent sample of US patients on hemodialysis demonstrates that patients in facilities with the least control of PTH, Ca, and P had the greatest risk of parathyroidectomy or the combination of cardiovascular hospitalization or death.